The Effects of Compensation, Competence, and Transformational Leadership on Lecturers’ Motivation and Performance - Wahyuddin, Wahyuddin; Arismunandar, Arismunandar; Ansar, Ansar (JURNAL AL-TANZIM, 2026)
This study aims to analyse the influence of compensation, competence, and transformational leadership on lecturer performance, with work motivation as an intervening variable. The study employed a quantitative approach using a cross-sectional survey and Structural Equation Modelling (SEM) to confirm the relationships among variables. Data were collected through a Likert-scale questionnaire from 289 lecturers at private Islamic universities in Indonesia. The instrument was developed based on indicators for each variable, validated by experts, and pilot-tested, demonstrating validity and reliability. The results indicate that compensation significantly influences work motivation, but does not directly impact performance; however, compensation influences performance through motivation. Competence significantly influences motivation and performance, and improves performance through motivation. Transformational leadership significantly influences motivation but does not directly impact performance; rather, it does so through motivation. Work motivation significantly influences lecturer performance. The implications of this study emphasise that improving lecturer performance can be achieved through policies that strengthen motivation, such as fair compensation, competency development, and transformational leadership.